Optimization Of Cruise Vehicle Loading As An Effort To Improve Ship Stability And Safety Sailing - Manungku Tri Pramudita; Tri Mulyanto (Veteran Justice Journal, 2021)
Abstract Load planning is one of the most important things in the world of shipping because it concerns the stability and safety of all crew and passengers on board. At the time of loading and unloading and when sailing, the ship always gets forces both from the cargo being unloaded and from objects and the surrounding nature: waves, currents, wind, collisions with docks, other ships or aground. These forces cause the ship to experience sway and other movements. In bad weather, these forces will get bigger and will cause the ship to capsize. So we need to know the ship's ability to deal with these forces and the possibility that the ship will capsize. Generally, passenger ships have more than enough stability to ensure that regulations are obeyed when the load is full but in practice sometimes ships can lose their stability when they are overloaded, because Therefore, the condition of the ship needs to be ensured in order to meet the existing minimum stability regulations. If this is not followed then the safety of the ship, crew and goods will be at stake. The purpose of this study is to describe the problems in ferry cargo arrangement as an effort to improve ship stability and safety and to determine the optimization of ferry cargo arrangement as an effort to improve ship stability and sailing safety. This research is a qualitative descriptive study, the data collection technique used is observation. , and literature, Data analysis techniques used Qualitative analysis techniques. Based on the explanation above, it can be concluded that the problems with the stability of ships include internal factors, namely factors originating from the ship itself, such as ship size, layout, leakage due to collision or aground, and so on. For this reason, the crew must pay attention to the location and weight of the goods before sailing. While external factors are external factors that affect the balance of the ship, such as natural conditions, waves, storms, and the like. Keywords: Assessment; Ship Stability; Ship Cargo; Sailing Safety